2010
DOI: 10.1093/annonc/mdp488
|View full text |Cite
|
Sign up to set email alerts
|

Assessing HER2 gene amplification as a potential target for therapy in invasive urothelial bladder cancer with a standardized methodology: results in 1005 patients

Abstract: Background: This study assessed the human epidermal growth factor receptor-2 (HER2) protein expression and its relationship with gene amplification in invasive bladder carcinoma, using the same criteria than for breast cancer.Patients and methods: In 1005 patients, paraffin-embedded tissues of transurethral resection or cystectomy were evaluated by immunohistochemistry (IHC), using antibodies against HER2. All samples with a 2+ or 3+ HER2 overexpression were evaluated by FISH.Results: HER2 overexpression was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
104
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(113 citation statements)
references
References 27 publications
2
104
3
2
Order By: Relevance
“…29 The HER2 protein is considered to have a significant role in bladder cancer outcomes, with HER2 protein expression reported in up to 31-65.5% of samples. 12,16,30 Furthermore, HER2 protein expression seems to correlate with tumor stage, tumor grade, [30][31][32] and poor prognosis. [30][31][32][33][34] One study found that the 5-year disease-free survival rate decreased from 48.5% in HER2-negative patients to 9.7% in those who were HER2 positive.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…29 The HER2 protein is considered to have a significant role in bladder cancer outcomes, with HER2 protein expression reported in up to 31-65.5% of samples. 12,16,30 Furthermore, HER2 protein expression seems to correlate with tumor stage, tumor grade, [30][31][32] and poor prognosis. [30][31][32][33][34] One study found that the 5-year disease-free survival rate decreased from 48.5% in HER2-negative patients to 9.7% in those who were HER2 positive.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there does not seem to be a strong association between HER2 protein expression and gene amplification in conventional urothelial carcinoma, 12 which is perhaps explained by the relative paucity of gene amplification found in conventional urothelial carcinoma specimens, ranging from only 5.1 to 22.2%. 12,[16][17][18] Sauter et al 35 found that even when urothelial carcinomas show HER2 amplification, there is extreme heterogeneity in the amount of amplification per cell, with areas of amplification 'clustering' together and the fraction of amplified cells ranging from 18-94% within tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13 ERBB2 amplification has been identified in other tumor types, although its role in treatment for these malignancies is yet to be defined. 10,[14][15][16] Although ERBB2 amplification has been identified in micropapillary urothelial carcinoma, its frequency and association with outcome has not been established in patients undergoing curative surgery. The objective of this study was to examine ERBB2 amplification and protein expression in a consecutive series of patients with micropapillary urothelial carcinoma undergoing radical cystectomy to determine the frequency of amplification and protein expression, and their association with outcome.…”
mentioning
confidence: 99%